2022
DOI: 10.1186/s12913-022-08798-2
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in compulsory hospitalisation – ethical challenges

Abstract: Background Compulsory hospitalisation in mental health care restricts patients’ liberty and is experienced as harmful by many. Such hospitalisations continue to be used due to their assumed benefit, despite limited scientific evidence. Observed geographical variation in compulsory hospitalisation raises concern that rates are higher and lower than necessary in some areas. Methods/discussion We present a specific normative ethical analysis of how ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…When meaningful comparisons are possible, research has also shown considerable variation in use in and between different countries and geographical areas ( 16 , 17 ). Geographical variation in the use of coercive interventions represents an ethical challenge in health services ( 18 ). Further, considerable conceptual and practical difficulties exist in understanding and researching compulsion and coercion.…”
Section: Introductionmentioning
confidence: 99%
“…When meaningful comparisons are possible, research has also shown considerable variation in use in and between different countries and geographical areas ( 16 , 17 ). Geographical variation in the use of coercive interventions represents an ethical challenge in health services ( 18 ). Further, considerable conceptual and practical difficulties exist in understanding and researching compulsion and coercion.…”
Section: Introductionmentioning
confidence: 99%
“…He argued that self-protection and the need to prevent harm to others are the only legitimate reasons to interfere with another person's freedom of action. In line with the principles of beneficence and non-maleficence developed by Beauchamp and Childress, several authors [44,77] suggest that the arguments for and against must be weighed, such that the use of coercive measures is only morally acceptable when the 'benefits' of protection or treatment outweigh the 'negative effects' on autonomy and the integrity of patients. Assessing the balance between promoting good (beneficence) and inflicting harm (maleficence) is, therefore, a primary ethical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…We know that previously committed patients have greater likelihood of later involuntary care, which may maintain the patterns of involuntary care without fully taking into account the patient’s symptoms or risks ([ 58 ] see Lived experience commentary by Olive & Nyikavaranda). Given the concerns voiced by user organizations [ 59 ], the ethical concern surrounding the provision of treatment without a person’s consent [ 60 , 61 ], and over geographical variations in such treatment [ 62 ] there is an urgent need for additional studies that test core assumptions of mental health acts.…”
Section: Discussionmentioning
confidence: 99%